Jernalderofringer fra Stavsager Høj ved Fæsted - en foreløbig præsentation af deponeringer og kontekster - Grundvad, Lars (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
In the winter of 2017/2018, a team of amateur archaeologists discovered a previously unknown site which contained several weapon deposits roughly dating to the period AD 150 – 550. Based on the data they had collected it was possible to narrow down four concentrations, of which three consisted mainly of various types of weapons. Museum Sønderskov has since excavated these three sites with financial support from the Danish Department of Castles and Culture The results are exciting. Not only has it been possible to excavate and rescue the weapon deposits from ploughing activities, it has also been possible to establish that a multi-phased well-founded longhouse was used for multiple depositions which actually consisted of more than just weapons. Equally interesting were three larger dark culture layers where especially one revealed the remains of an intense destruction of copper alloy artifacts such as belt fittings, brooches, parts of drinking horns etc. This paper is a preliminary presentation of the results of the surveys which have been conducted at this newly found site. Furthermore, it is a presentation of the theory that these deposits are part of the pre-Christian rituals carried out in a region that today is named after the god Frey. A series of depositions where the gold hoard »The Fæsted Hoard« from the 10th century is the so far youngest.